2017
DOI: 10.1080/10641963.2017.1306539
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol alleviates aortic remodeling through eNOS upregulation and inhibition of oxidative stress in l-NAME-induced hypertensive rats

Abstract: Our data indicate a protective role of nebivolol on the high blood pressure and vascular remodeling induced by l-NAME. The beneficial vascular effect of nebivolol is mediated by the upregulation of eNOS and inhibition of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
0
13
1
1
Order By: Relevance
“…β3 AR s are upregulated in the myometrium during pregnancy, potentially heightening this effect. Nebivolol further enhances endothelial nitric oxide synthase ( eNOS ) expression and activity . This resulting surge of nitric oxide increases total protein S‐nitrosations ( SNO s), promoting SNO ‐mediated myometrial smooth muscle relaxation .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…β3 AR s are upregulated in the myometrium during pregnancy, potentially heightening this effect. Nebivolol further enhances endothelial nitric oxide synthase ( eNOS ) expression and activity . This resulting surge of nitric oxide increases total protein S‐nitrosations ( SNO s), promoting SNO ‐mediated myometrial smooth muscle relaxation .…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol further enhances endothelial nitric oxide synthase (eNOS) expression and activity. 11 This resulting surge of nitric oxide increases total protein S-nitrosations (SNOs), 12 promoting SNO-mediated myometrial smooth muscle relaxation. 9 Inhibition of S-nitrosoglutathione reductase (GSNOR) also increases nitric oxide availability, which relaxes myometrial tissue 6 ; however, nebivolol does not inhibit the SNO-metabolizing enzymes GSNOR or thioredoxin reductase (TrxR) BARNETT AND BUXTON | 6393 N = 4), or mouse ( Figure 1B), myometrium.…”
Section: Nebivolol Decreases Uterine Force and Aucmentioning
confidence: 99%
See 2 more Smart Citations
“…NO is an important regulator of vascular tone and blood pressure. It has been reported that the pharmacological reduction of NO can lead to hypertension in normotensive rats (Raghavan and Dikshit, 2004;Wang et al, 2017). L-NAME administration decreases NO synthesis and develops hypertension in rats (Leo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%